1991
DOI: 10.1128/jb.173.7.2297-2300.1991
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic effects of a relC mutation in Streptomyces antibioticus

Abstract: Ochi (Agric. Biol. Chem. 51:829-835, 1987) has isolated a relaxed mutant of Streptomyces antibioticus, designated relC49. relC49 accumulates significantly lower levels of ppGpp than the parent stain, IMRU3720. At its maximum, the ppGpp level in relC49 was only one-fourth that observed in strain IMRU3720. Interestingly, a burst of ppGpp synthesis between 18 and 22 h of growth in IMRU3720 coincided with the onset of actinomycin production in that strain. As shown previously, the activity in protein synthesis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
16
0
1

Year Published

1994
1994
2009
2009

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 20 publications
6
16
0
1
Order By: Relevance
“…In addition, the relaxed mutant contained decreased levels of two enzymes involved in the biosynthesis of actinomycin, phenoxazinone synthase and actinomycin synthetase I (22,28). In the parental strain of S. antibioticus, there was a significant increase in ppGpp levels just prior to the onset of actinomycin production (22). Thus, studies of wild-type S. antibioticus as well as relaxed mutants support a relationship between ppGpp production and actinomycin biosynthesis.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…In addition, the relaxed mutant contained decreased levels of two enzymes involved in the biosynthesis of actinomycin, phenoxazinone synthase and actinomycin synthetase I (22,28). In the parental strain of S. antibioticus, there was a significant increase in ppGpp levels just prior to the onset of actinomycin production (22). Thus, studies of wild-type S. antibioticus as well as relaxed mutants support a relationship between ppGpp production and actinomycin biosynthesis.…”
mentioning
confidence: 63%
“…Ochi isolated a relaxed (relC) mutant of S. antibioticus IMRU 3720 some years ago and demonstrated that this mutant contained reduced levels of ppGpp compared with the parental strain and was unable to synthesize actinomycin (28,29). In addition, the relaxed mutant contained decreased levels of two enzymes involved in the biosynthesis of actinomycin, phenoxazinone synthase and actinomycin synthetase I (22,28). In the parental strain of S. antibioticus, there was a significant increase in ppGpp levels just prior to the onset of actinomycin production (22).…”
mentioning
confidence: 99%
“…To further examine this possibility, it is desirable to obtain mutants in which the production of ppGpp is reduced to negligible levels or is completed eliminated. Such is not the case in the relC49 mutant (15,20). An additional drawback of relC mutants is that the effect of the mutation on ppGpp production in those constructs is indirect.…”
mentioning
confidence: 89%
“…The relC49 mutant was also found to lack detectable levels of actinomycin synthetase I, another enzyme involved in actinomycin biosynthesis (15). In the parental strain of S. antibioticus, there was a significant increase in ppGpp levels just prior to the onset of actinomycin production (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation